Elite Puri dalam Lanskap Politik Kontemporer di Bali - I Putu Gede Suwitha (Pusat Kajian Bali Universitas Udayana, 2015)
AbstractThere is been few studies on the role of local or traditional elites in Bali in the context of national politics in Bali. It seems that the traditional Balinese elites played a dominant role inthe context of political culture in the past, particularly sincethe fall of Bali in the fourteenth Century until nineteenth century. However, this situation has still developed inthe recent situation and will be in the future. This study concentrates on the role of the traditional Balinese elites in the context of recent situation in terms of democracy and the involvement of the elites particularly after the reformation period and also trying to show to what extent the role of the traditional Balinese elite in terms of democracy in modern politics.